Factors that Influence the Choice of Treatment for Patients with Urethral Stricture (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The aim of our study was to determine the factors affecting to the choice of treatment of patients with urethral stricture.We conducted a retrospective analysis of case histories of 109 patients with urethral stricture, which were carried out various kinds of operations on the urethra. 53 patients underwent endoscopic recanalization of the urethra under fluoroscopic guidance, followed by transurethral resection of the stricture zone, 23 - transurethral internal optical urethrotomy, 33 - different types of urethroplasty.The results showed that the main factors influencing to the choice of treatment of patients with urethral stricture are the patient's age, presence of concomitant diseases, the degree of anesthetic risk surgery, localization and extent of the stricture.